Green synthesis and antibacterial effect of silver nanoparticles using Vitex negundo L. - Zargar, Mohsen (MDPI, 2011)
Different biological methods are gaining recognition for the production of silver nanoparticles (Ag-NPs) due to their multiple applications. One of the most important applications of Ag-NPs is their use as an anti-bacterial agent. The use of plants in the synthesis of nanoparticles emerges as a cost effective and eco-friendly approach. In this study the biosynthesis of silver nanoparticles using Vitex negundo L. extract and its antimicrobial properties has been reported. The resulting silver particles are characterized using transmission electron microscopy (TEM), X-ray diffraction (XRD) and UV–Visible (UV-Vis) spectroscopic techniques. The TEM study showed the formation of silver nanoparticles in the 10–30 nm range and average 18.2 nm in size. The XRD study showed that the particles are crystalline in nature, with a face centered cubic (fcc) structure. The silver nanoparticles showed the antimicrobial activity against Gram positive and Gram negative bacteria. Vitex negundo L. was found to display strong potential for the synthesis of silver nanoparticles as antimicrobial agents by rapid reduction of silver ions (Ag+ to Ag0).